PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA RAHAYU PHOTO COPY DENGAN METODE MySQL - Mohammad Ahmadar; Perwito (Program Studi Informatika Universitas Teknologi Sumbawa, 2021)
Abstract: The research aims to build a sales information system on the Rahayu Photo Copy based on the web. The system was developed using the PHP programming language using MySQL as a database. The method of data collection is done by way of interviews, observation, and coupled with a study of the library which has a connection with the problems faced. While the research method used is the descriptive qualitative research with the Waterfall model development system.From research conducted, found problems such as; 1) Often lost transaction notes, 2) not regularly structured sales transactions, and 3) Manual recording is not neat, resulting in difficulties in recording transactions and also errors in recording the end of month reports. The effort to solve this problem is by creating a web-based sales information system using MySQL. Keyword: Design of information system, Purchasing, Raw materials, MySQL.